1995
DOI: 10.1002/adma.19950071009
|View full text |Cite
|
Sign up to set email alerts
|

Self‐assembled crystalline monolayers and multilayers of n‐alkanes on the water surface*

Abstract: It has long been believed that the formation of Langmuir monolayers at the air-water interface is limited to amphiphilic molecules containing a hydrophobic chain and a hydrophilic headgroup, such as OH or COOH, which interacts with the subphase.['] These materials have pressure-area (17-A) isotherms which give an average area per molecule corresponding to monolayer coverage. Recently, isotherm and grazing-incidence X-ray diffraction data have been reported indicating monolayer formation for the non-amphiphilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 21 publications
5
69
1
Order By: Relevance
“…These very small crystals are generally unstable due to their high surface tension, and thus have a tendency to transform to larger particles by Oswald ripening. In recent years, quantum dots were prepared mainly in matrices and also as self-assembled structures, such as reverse micelles, [10] zeolites, [11] polymers, [12] self-assembled monolayers, [13] biopolymers, [14] layered metal phosphonates, [15] and Langmuir±Blodgett (LB) films. [16,17] In the preceding communication, [18] we reported that spreading of tetracosanedioic acid HOOC(CH 2 ) 22 COOH (C 24 diacid) on surfaces of aqueous solutions containing di- …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These very small crystals are generally unstable due to their high surface tension, and thus have a tendency to transform to larger particles by Oswald ripening. In recent years, quantum dots were prepared mainly in matrices and also as self-assembled structures, such as reverse micelles, [10] zeolites, [11] polymers, [12] self-assembled monolayers, [13] biopolymers, [14] layered metal phosphonates, [15] and Langmuir±Blodgett (LB) films. [16,17] In the preceding communication, [18] we reported that spreading of tetracosanedioic acid HOOC(CH 2 ) 22 COOH (C 24 diacid) on surfaces of aqueous solutions containing di- …”
Section: Methodsmentioning
confidence: 99%
“…Recently, the formation at the air±water interface of crystalline monolayer and multilayer films obtained from symmetric molecules with end groups equally hydrophobic or hydrophilic, such as long-chain linear fluorocarbons [14] and hydrocarbons, [15] oligothiophenes [16] (containing four, five, and six rings), and a,w-alkanediols, [17] has been reported. In these films at low surface pressure the long molecular axis is aligned either normal to the water surface or tilted by up to 40 from the normal.…”
mentioning
confidence: 99%
“…These crystallites self-assemble spontaneously at zero surface pressure from excess material placed on water for 20 ϽnϽ30. 17,22 Mercury as a subphase for Langmuir films offers several additional advantages. The high surface energy of mercury, 500 mJ/m 2 , as compared to that of water, 72 mJ/m 2 , should enhance the spreading of surface films, and induce spreading in compounds not readily, or not at all, spreadable on water.…”
Section: Introductionmentioning
confidence: 99%
“…12,23,24 For comparison we also study structural and dynamical water behavior at extended hydrophilic surfaces ͑macroscopic contact angle ls Ͻ10°). 19,42 Specifically, our present simulations include explicit TIP3 43 water molecules confined between the crystalline materials n-C 36 H 74 ͑hydrophobic͒ 19,44 and n-C 35 H 71 OH ͑hydrophilic͒. 45 The observed difference between water behavior in the two cases is discussed in the perspective of the hydrophobic effect.…”
Section: Introductionmentioning
confidence: 99%